1995
DOI: 10.1007/bf02893583
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B and D are localized at the surface of human breast cancer cells

Abstract: Alterations in trafficking of cathepsins B and D have been reported in human and animal tumors. In MCF10 human breast epithelial cells, altered trafficking of cathepsin B occurs during their progression from a preneoplastic to neoplastic state. We now show that this is also the case for altered trafficking of cathepsin D. Nevertheless, the two cathepsins are not necessarily trafficked to the same vesicles. Perinuclear vesicles of immortal MCF10A cells label for both cathepsins B and D, yet the peripheral vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 28 publications
8
55
0
1
Order By: Relevance
“…These results are similar to those reported for catB in human breast carcinoma cells (Sameni et al, 1995) and in U87 human glioma cells (Rempel et al, 1994).…”
Section: Cathepsin B Is Localized On the Surface Of Differentiating Msupporting
confidence: 91%
See 2 more Smart Citations
“…These results are similar to those reported for catB in human breast carcinoma cells (Sameni et al, 1995) and in U87 human glioma cells (Rempel et al, 1994).…”
Section: Cathepsin B Is Localized On the Surface Of Differentiating Msupporting
confidence: 91%
“…To determine if catB is localized on the surface of differentiating myoblasts, we used an established protocol for the staining of surface proteins that does not permeabilize the cells and permits the differentiation of cell surface catB from lysosomal catB (Sameni et al, 1995) (Figure 6). Using this method, catB was detected as discrete containing Z-Arg-Arg-NHMec substrate and pericellular catB activity was measured continuously for 10-15 min at 378C.…”
Section: Cathepsin B Is Localized On the Surface Of Differentiating Mmentioning
confidence: 99%
See 1 more Smart Citation
“…11 There is evidence of altered trafficking of CatB in glioblastomas, with a redistribution of enzyme to the cell periphery. 12 In addition, a potential role in invasion has been suggested by high levels at the tumor periphery and in infiltrating cells. 6 The closely related cysteine proteinase cathepsin L (CatL) has also been implicated in glioblastoma invasion in an in vitro model.…”
mentioning
confidence: 99%
“…Cathepsin D (CathD), an aspartyl lysosomal protease expressed in all tissues is secreted from carcinomas. A large number of independent clinical studies associated high Cath-D concentrations in primary breast cancers with increased risk of subsequent metastasis (14). Analysis of glycosylation of Mucinl and trafficking of the lysosomal enzyme Cath-D in COG3 KD breast cells line revealed that disturbance of COG complex function in HB2 cells lead to abnormalities of glycoprotein processing for Mucinl and its secretion into the medium ( Figure 5).…”
mentioning
confidence: 99%